(untitled) (Comprehensive Journal of Science, 2025)
The objective of this research was to examine the influence of the Human Resource Information System (HRIS) on the degree of managerial executives’ focus on assessing staff performance within Al-Marqab Universit. . It employed a descriptive-analytical methodology, relying on a survey instrument for gathering the required information. A deliberate sampling method was applied to choose administrative executives from Al-Marqab University, resulting in a group of 45 participants. Data from the study were processed and evaluated using the SPSS statistical program. The study yielded several key findings, most notably: A statistically significant impact of the HRIS on employee performance evaluation, with an effect size of 75.6%. A statistically significant impact of administrative leadership’s attention to employee development on performance evaluation, with an effect size of 13.5%. A statistically significant impact of the HRIS on the level of administrative leadership’s attention to employee development, with an effect size of 13.3%. A statistically significant effect of certain demographic characteristics of the study sample on their opinions regarding the study variables. Additionally, the study revealed that the level of administrative leadership’s attention to employee development was moderate from the participants’ perspective, with a mean response value of 1.85 according to the three-point Likert scale. The HRIS level was considered low, with a mean response of 1.6, and the level of employee performance evaluation was also deemed low, with a mean response of 1.598 on the same scale.